A study on factors influencing medico legal opinion in alleged sexual abuse - Kitulwatte, I.D.G.; Wijewardena, H.P.; Edirisinahe, P.A.S.; Senarathne, U.D. (My University, 2016)
Attached

Background: Aim of medico-legal examination in alleged sexual abuse is providing an opinion on physical/sexual contact between individuals. Supportive scientific evidence is often absent and experts are in a dilemma. Objectives: To identify the limitations of medico legal opinion in alleged sexual abuse and the factors influencing these limitations. Methods: A retrospective descriptive study based on medico-legal case records of females who had been referred to a Teaching Hospital in the Western province of Sri Lanka following an allegation of sexual abuse during a period of 3 years (2012-2015). Data analysis was done with Statistical Package for Social Sciences (SPSS). Results: Out of 441 medical records perused, the main complaint (n=180, 40%) was related to concerns of the guardians. Majority (n=302, 68%) had presented for medico-legal examination 72-hours after the incident. Giving a firm positive medico legal opinion as per the complaint had been possible in 280(63%). A firm opinion could not be given in 19 (86%) out of 22 victims reporting intracrural intercourse and for 22 (79%) out of 28 victims complaining of fingering. Out of 376 victims with no recent injuries, 276 (73%) presented late. Out of the 128 victims who had experienced physical threats, only 35 (27%) had supportive injuries. Conclusions: Many factors including late presentation and type of complaint influence the medico legal opinion in a case of sexual abuse and therefore it is a challenge to the forensic expert. Thus, proper administration of justice needs an insight into these factors, challenges and the limitations.